Organising pneumonia in Rhupus syndrome. Issue 12 (19th December 2019) - Gutta, Smitesh; Das, Sohini; Kodiatte, Thomas Alex; Vimala, Leena Robinson
Abstract : Interstitial lung disease (ILD) is seen in 17% of patients with Rhupus syndrome. Organising pneumonia (OP), a subtype of connective tissue disease-associated ILD, is rare but associated with good outcomes. Here, we present a patient with Rhupus who developed OP.